2007
DOI: 10.1007/s10750-007-0770-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two different flood pulses on planktonic communities of the largest floodplain lakes of the Daugava River (Latvia)

Abstract: An impact of two different flood pulses on phyto-and zooplankton communities of the two largest floodplain lakes of the Daugava River were studied in the spring and summer of 2005. Samples of phyto-and zooplankton were taken at weekly and biweekly intervals. At the end of March, a medium size pulse of spring flood was observed. At the beginning of May, it was followed by an unusually high pulse of flush floods caused by heavy rainstorms in the local drainage area. An overall increase of biomass and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
2
25
1
Order By: Relevance
“…Relationship between community attributes and water level: The associations of community attributes identified in this study (species richness, Shannon diversity index, evenness, and abundance) were also reported by Paidere et al (2007) and Lindholm et al (2007). These relationships characterize the behaviour of the zooplankton community according to two main scenarios: (i) at low abundances, fauna uniformly distributed, evenness increases, an increase in the diversity index is favoured, and species coexistence is promoted by minimizing competitive exclusion (Paidere et al 2007); (ii) at high abundances, few species predominate, which decreases the evenness and the diversity of species.…”
Section: Macrothrix Elegans Sars 1901 Copepodasupporting
confidence: 64%
See 1 more Smart Citation
“…Relationship between community attributes and water level: The associations of community attributes identified in this study (species richness, Shannon diversity index, evenness, and abundance) were also reported by Paidere et al (2007) and Lindholm et al (2007). These relationships characterize the behaviour of the zooplankton community according to two main scenarios: (i) at low abundances, fauna uniformly distributed, evenness increases, an increase in the diversity index is favoured, and species coexistence is promoted by minimizing competitive exclusion (Paidere et al 2007); (ii) at high abundances, few species predominate, which decreases the evenness and the diversity of species.…”
Section: Macrothrix Elegans Sars 1901 Copepodasupporting
confidence: 64%
“…These relationships characterize the behaviour of the zooplankton community according to two main scenarios: (i) at low abundances, fauna uniformly distributed, evenness increases, an increase in the diversity index is favoured, and species coexistence is promoted by minimizing competitive exclusion (Paidere et al 2007); (ii) at high abundances, few species predominate, which decreases the evenness and the diversity of species. Water level influences the community dynamic, decreasing the total abundance but increasing the diversity of species.…”
Section: Macrothrix Elegans Sars 1901 Copepodamentioning
confidence: 99%
“…Field surveys have been conducted on the influence of shortterm rainfall on algal blooms and the phytoplankton community. For example, Nõges et al (2011) showed that precipitation increased nutrient levels and algal biomass in Lake Varese and Paidere et al (2007) reported that floods increased phytoplankton diversity and decreased phytoplankton biomass in two floodplain lakes. In addition, the effects of nutrients on phytoplankton communities have been compared among different water bodies in the same area: Gikuma-Njuru et al (2013) revealed that the Nyanza Gulf of Lake Victoria was P-deficient and dominated by non-nitrogen-fixing cyanobacteria, whereas Lake Victoria as a whole was N-deficient and occupied by diazotrophic cyanobacteria and diatoms.…”
Section: Introductionmentioning
confidence: 99%
“…Cryptomonads are also able to better capture nutrients because of their ability to mixotrophy (Jones 2000). Dominant Cryptophyta are common in many oxbow lakes (Paidere et al 2007;Pithart et al 2007;BovoScomparin and Train 2008;Krasznai et al 2010), which may be due to their high tolerance to different trophic conditions and resistance to shade in the water column. Cryptomonads are very sensitive to predation by zooplankton communities (Reynolds et al 2002;Reynolds 2006;Padisák et al 2009).…”
Section: Macrophytesmentioning
confidence: 99%